2012
DOI: 10.1161/strokeaha.111.640946
|View full text |Cite
|
Sign up to set email alerts
|

Valid Items for Screening Dysphagia Risk in Patients With Stroke

Abstract: Background and Purpose-Screening for dysphagia is essential to the implementation of preventive therapies for patients with stroke. A systematic review was undertaken to determine the evidence-based validity of dysphagia screening items using instrumental evaluation as the reference standard. Methods-Four databases from 1985 through March 2011 were searched using the terms cerebrovascular disease, stroke deglutition disorders, and dysphagia. Eligibility criteria were: homogeneous stroke population, comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
130
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(154 citation statements)
references
References 36 publications
4
130
0
8
Order By: Relevance
“…Screening is the essential first step in identifying risk of dysphagia that expedites referral to speech pathology for evaluation and treatment (31). As for the BBDST-R, it has already been implemented in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Screening is the essential first step in identifying risk of dysphagia that expedites referral to speech pathology for evaluation and treatment (31). As for the BBDST-R, it has already been implemented in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Early identification of dysphagia provides early intervention therefore contributes to reduce dysphagia complications, length of hospital stay, and healthcare costs especially for patients with neurological patients. 21 We found that the T-EAT-10 correlated with PAS scores, which means that neurological patients with aspiration presented higher scores in T-EAT-10. To support our findings, we investigated the sensitivity and specificity of the T-EAT-10.…”
Section: Discussionmentioning
confidence: 61%
“…However, a recent review identified valid elements for screening for dysphagia risk and also identified a water swallow test as being an important part of the screen. 2 The protocol as shown in the CDS flow chart includes a water swallow test and also many non-swallow elements (e.g. dysarthria) identified in the review as valid screening items.…”
Section: Interventionmentioning
confidence: 99%